2009
DOI: 10.1002/qre.1013
|View full text |Cite
|
Sign up to set email alerts
|

Some results on the variogram in time series analysis

Abstract: Data used for monitoring and control of industrial processes are often best modeled as a time series. An important issue is to determine whether such time series are stationary. In this article we discuss the variogram-a graphical tool for assessing stationarity. We build on previous work and provide further details and more general results including analytical structures of variogram for various non-stationary processes, and illustrate with a number of examples of variograms using standard data sets from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…However, it can be shown that not every non-stationary process possesses a variogram. For instance, see 7 for an example of ARIMA process for which variogram is not defined.…”
Section: Background On the Variogrammentioning
confidence: 99%
See 1 more Smart Citation
“…However, it can be shown that not every non-stationary process possesses a variogram. For instance, see 7 for an example of ARIMA process for which variogram is not defined.…”
Section: Background On the Variogrammentioning
confidence: 99%
“…. Further, Box and Luceno 4 and Khachatryan and Bisgaard 7 provide analytic expressions for the standardized variogram for ARIMA processes. Specifically, Khachatryan and Bisgaard 7 show that the standardized variogram is always defined for autoregressive integrated moving average processes ARIMA(p, d, q) for any value of p and q and for d ≤ 1.…”
Section: Background On the Variogrammentioning
confidence: 99%
“…Besides the common second-order moments used to describe the random process {X t , t ∈ T}, such as the autocovariance function and the autocorrelation function, the variogram can also be considered and even preferred with respect to covariance function [10,19].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In this context, the use of geostatistical techniques could also be convenient, nevertheless these techniques are usually applied to analyze, through the variogram, spatial relationships among sample data measured at some locations in a domain and to predict the corresponding spatial phenomena [6,18,22,29]. In particular, the variogram could represent a complementary exploratory tool for assessing stationarity in time series [2,19] and it has the considerable advantage that it is defined in much wider circumstances than the autocovariance and the autocorrelation. Moreover, this analytical tool is appropriate to identify trends and periodicity exhibited by the data and to obtain kriging predictions of the variable under study, either for temporal intervals with missing values (interpolation mode) and in time points after the last available data (extrapolation mode).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation